2019
DOI: 10.1177/2167479519852605
|View full text |Cite
|
Sign up to set email alerts
|

“We All Go Through It”: Media Depictions of Mental Illness Disclosures From Star Athletes DeMar DeRozan and Kevin Love

Abstract: Mental illness remains stigmatized in the United States and abroad, with the mass media often blamed for perpetuating stereotypes about people who experience mental health issues. 2018 witnessed two professional basketball players—star athletes DeMar DeRozan and Kevin Love—disclosing personal experiences with depression and anxiety. Informed by social cognitive and framing theories, the present study examined how news stories characterized the disclosures, examining ways in which journalists presented the athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 45 publications
7
45
0
Order By: Relevance
“…Brown and Basil (1995) concluded that superstar Magic Johnson's 1991 disclosure of his HIV-positive status and advocacy for preventative education lessened stigma around HIV/AIDS and promoted avoidance behaviors linked to its transmission. This research, along with Parrott et al's (2019) findings that Love's initial disclosure was positively received, demonstrates that studying Love's mental health advocacy is important because NBA players contribute to larger public health conversations.…”
Section: Studying Mental Health Discoursementioning
confidence: 67%
“…Brown and Basil (1995) concluded that superstar Magic Johnson's 1991 disclosure of his HIV-positive status and advocacy for preventative education lessened stigma around HIV/AIDS and promoted avoidance behaviors linked to its transmission. This research, along with Parrott et al's (2019) findings that Love's initial disclosure was positively received, demonstrates that studying Love's mental health advocacy is important because NBA players contribute to larger public health conversations.…”
Section: Studying Mental Health Discoursementioning
confidence: 67%
“…In recent examinations, research has focused on the media coverage surrounding professional athletes and their public disclosures of mental health concerns. Parrott et al (2019) conducted a content analysis of media coverage surrounding NBA players DeMar DeRozan, Kevin Love, and their public discussion of mental health during the 2017–2018 NBA season. Their findings indicated that news stories framed the athletes as possessing character strength for their disclosures.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Therefore, White’s and DeRozan’s public discourse on mental health is an opportunity to examine how mental health is discussed within the United States and an opportunity to analyze the coverage of NBA players. While prior research has compared media coverage of NBA players and their mental health (Parrott et al, 2019), there is yet to be an examination into how two African American athletes are covered in regard to their mental health. This is an important area of examination because prior research has established that the African American population in the United States perceives mental health differently than the White population (Anglin et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two dominant frames were identified, leveraging of socio-political capital to regulate the sport and protect society from itself and the framing of public officials as protectors of social citizenry. Finally, recent media framing of mental health issues in sport has been shown to be supportive of athletes, challenging inaccurate assumptions concerning mental illness and calling for greater support for athletes who experience mental illness (Parrott et al, 2019).…”
Section: Media Framing Of Concussionmentioning
confidence: 99%